2019
DOI: 10.1021/acs.organomet.9b00207
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly toward Nanoparticles of a Chiral Palladium Supramolecular Complex Based on Bicyclo[3.3.1]nonane Framework

Abstract: The cyclic supramolecular coordination constructs were synthesized via metal-directed self-assembly from cis-protected Pd(II) precursor and chiral and racemic C 2 symmetric V-shaped bicyclo[3.3.1]nonane-based ligands incorporating pyridyl groups. In the complexes, these ligands act as bridges to connect together metal centers resulting in dinuclear and tetranuclear assemblies capable of further hierarchical aggregation on surfaces as well as in solution. Supramolecular structures obtained were characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…39 Moreover, we observed that charged complexes aggregated into nanoparticles because the charged molecules lowered the surface tension of the solution. 40 A closer look at the catalytic active site during the simulation gives a further possible clue to the passivity of GOx in DMSO and DMF, in contrast with the other organic solvents: the ability of these polar solvents to block the active site. Fig.…”
Section: Molecular Dynamics Simulations Of Gox In the Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Moreover, we observed that charged complexes aggregated into nanoparticles because the charged molecules lowered the surface tension of the solution. 40 A closer look at the catalytic active site during the simulation gives a further possible clue to the passivity of GOx in DMSO and DMF, in contrast with the other organic solvents: the ability of these polar solvents to block the active site. Fig.…”
Section: Molecular Dynamics Simulations Of Gox In the Solventsmentioning
confidence: 99%
“…39 Moreover, we observed that charged complexes aggregated into nanoparticles because the charged molecules lowered the surface tension of the solution. 40…”
Section: Molecular Dynamics Simulations Of Gox In the Solventsmentioning
confidence: 99%
“…[9] The resulting chiral metallosupramolecular structure is unlikely to racemize since its chirality is intended by the use of an enantiopure chiral ligand prior to the self-assembly reaction. Various chiral bridging ligands that include chiral amino acid derivative (N1), [50] BINOL (N25), [51] binaphthyl derivatives (N26), [52] and rigid bicyclo[3.3.1] nonane bridges (N27), [53] have been utilized to efficiently yield chiral metallomacrocycles. Representative examples of chiral ligands are presented in Figure 5.…”
Section: Chiral and Other Achiral N-ligandsmentioning
confidence: 99%
“…Orentas and co‐workers reported a dinuclear Pd(II) cycle by using a V‐shaped bicyclo[3.3.1]nonane‐based spacer with bis‐ethynylpyridine coordinating motifs (L 7 ) [24] . The self‐assembly of [ 7 ] 4+ was carried out using cis ‐protected Pd(II) to ensure the formation of a discrete cycle.…”
Section: Bicyclic Organic Spacer Based Ligands and Its Sccsmentioning
confidence: 99%